The Use of Enzymatic Pre-digestion of Fermented Palm Kernel Cake in the Laying Hens Diet on Production Performance, Nutrient Digestibility, Egg Quality, and Egg Chemical Content - Sundu, B.; Adjis, A.; Hafsah, H.; Pamulu, M. (Faculty of Animal Science, IPB University, 2024)
A study was conducted to determine the effect of enzymatic pre-digestion of fermented palm kernel cake in the laying hen’s diet on the performance production, nutrient digestibility, egg quality, and egg chemical content. Palm kernel cake (PKC) was added with 3% ammonium sulfate and then fermented by using Saccharomyces cerevisiae for 5 days (FPKC). The FPKC was hydrolyzed with mannanase to produce enzymatic pre-digestion of FPKC (EPFPKC). The study used a completely randomized design with 5 treatments and 6 replications. The EPFPKC-containing diets were fed to 240 Lohmann Brown laying hens aged 19 weeks old for 3 months. The diets were D-1 (without EPFPKC), D-2 (5% EPFPKC), D-3 (10% EPFPKC), D-4 (15% EPFPKC), and D-5 (20% EPFPKC). Feed and drinking water were available at all times. Total fecal discharges were collected for three consecutive days to measure feed digestibility. The variables measured were feed digestibility, production performance, egg quality, lauric acid, cholesterol, and beta-carotene content of eggs. Data were analyzed with the variance analysis. The results showed that fermentation could increase the protein content of PKC and decrease the crude fiber content. The addition of EPFPKC in the diets increased dry matter, protein, and crude fiber digestibility and improved the quality of albumen and yolk during 28 days of storage at room temperature. Adding EPFPKC also increased the concentration of lauric acid and beta-carotene in eggs. In conclusion, the addition of 15% of enzymatic pre-digestion of fermented palm kernel cake (D-4) in the diet improves the quality of eggs stored for 28 days, and increases the concentration of lauric acid and beta carotene in eggs.